Coordination of technology of railway operation of the Republic of Tajikistan and organization of railways in international traffic - P. N. Pulatov (Вестник Научно-исследовательского института железнодорожного транспорта)
Current geopolitical and economic conditions for the functioning of railway transport in most post-Soviet states are such that it is extremely difficult to provide required quality of transport services and break-even operations at high expenses for maintaining the railway infrastructure and rolling stock. Dynamics of transportation of the Tajik Railway (TSR) is shown, which displays that most of its sections are classified as low-intensity ones. The paper proposes methodical principles, setting and qualitative analysis of the task of rationalization of operational work and organization of car flows for international transportation, taking into account the specifics of the Tajik Railway. There is a problem of complex maintenance of the efficiency of operational work in modern conditions based on the synthesis of the tasks of self-management (rational internal operational technology of the Tajik Railway) and coordination tasks (technological interaction with railway administrations of other states). Author substantiated the necessity of solving this problem. Proposed classification of technological restrictions and controlled variables in the performance of transport takes into account methods for changing external conditions for the functioning of the railway landfill and methods for increasing internal efficiency of its operation. The search for the solution of the problem involves direct search of variants along its ordered set with clipping of groups of variants that do not correspond to constraints, with the subsequent finding of compromise control over a set of effective alternatives.